Human papilloma virus vaccination: knowledge, awareness and acceptability among medical and paramedical students - Hoblidar, Suchith; Moni, Suma S.; Desai, Rathnamala M.; Neravi, Asha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Cervical cancer is the second leading cause of death in india. it is also one of the few malignancies where an infectious etiological agent human papilloma virus (HPV) has been identified. With the advent of HPV vaccination, it is possible to reduce the morbidity and mortality associated with carcinoma cervix. But biggest hurdle to achieve this is the lack of awareness about the availability and use of HPV vaccine. This study was conducted to know knowledge and awareness of HPV infection and vaccination among medical and paramedical students. We also evaluated the acceptability and coverage of HPV vaccine among these students. Methods: This study was conducted among a total of 520 female students of the Sri Dharmasthala Manjunatheshwara University with the help of a questionnaire. The study group included 207 MBBS students, 167 BDS students, 89 nursing students and 57 physiotherapy students. Results: Most of the students were in 18-20 years’ age group. Nearly 40.57% of the students knew that HPV is sexually transmitted and 29.80% were aware that this infection can be prevented. Availability of HPV vaccine was known to 75% of the students and the main source of their information was through their college teachings. Nearly 43.75% of the students knew HPV vaccine protects against cervical cancer and 26.73% of the students were vaccinated. Overall knowledge and awareness were better among medical students. Conclusions: A lot of work needs to be done so as to make the target population accept HPV vaccine. There is a great difference between awareness of availability of the vaccine and its use. This emphasizes the need for health care professionals to take special interest in promoting this vaccine in the general population.